THE POSITIVE EFFECT ON THE PLANT AND YIELD BY TREATING WHEAT SEEDS WITH SALT WATER - Aiad Abdelkareim Akhreim Alzway, Ghazala Ahmad Hamaden Mansour, (Chelonian Research Foundation, 2024)
Salt stress often causes serious problems in wheat production areas. Salinity is one of a major threat in harvesting good wheat stand. In this study, potential of seed priming techniques to improve the performance of wheat in a saline field was tested. this is seed priming is a technique which is used to improve seed germination in field. Results indicated that wheat sown under effects of sea water An experiment was conducted on the Seed wheat For priming, wheat seeds were soaked in sea water solution . For comparison, also untreated seeds were also taken as control. Seed priming treatments. Seeds were primed for 6,12 and 24 hours at three concentration sea water (salinity of water) (25, 50 ,75 and 100) and distilled water as control). Maximum seed germination percentage in lower dilutions was observed when the seeds primed by 0.0,25,50 dilutions of sea water, The most stem length was obtained for seeds . Maximum (MGT) of wheat was obtained from seeds primed with sea water 25 and 50found the increases, value germination was improved increases on lower concentration 25,50 include control. Keywords: wheat, triticum aestivum, Salinity of water priming, salt stress, root,shoot.